Notes on Early Architectural Phenomenology of Christian Norberg-Schulz - Tourek, Jiří (Actual Problems of Theory and History of Art, 2016)
Phenomenology in architecture — and in theory of architecture in particular — is a result of reaction to late modernism. Christian Norberg-Schulz, an architect and one of world leading theoretician of his days, proposed in his theories a new basis for architecture. At the beginning, there was structuralism and semiotics in his first book, Intentions in Architecture, but very soon he shifted his interest to phenomenology (and Heidegger) and started to build his phenomenological theory. His first book on the theme was Existence, Space and Architecture; and since then he went on developing phenomenology in architecture for his whole life.The aim of the article is — working from the point of view of a theoretician of architecture much informed in philosophy — to show the basis of his theory and the problems found within it. The text is derived predominantly from the book Existence, Space and Architecture, but takes into consideration his other theoretical works. The author pays special attention to the role of modernity in Norberg-Schulz’s theory. This is paradoxical, since his aim was to provide new basis for modern and contemporary architecture, but this basis was constructed on hypothetical pre-modern experience of architecture. The key question of the article is whether modernity was a break from the tradition (as modernists believed) or some form of continuity (as proposed by Norberg-Schulz) and if it’s possible to ground contemporary architecture on the same basis as before modern times. Norberg-Schulz’s attitude towards modernity shows limits of his theory and makes him a problematic source of ongoing phenomenological project in architecture. As his theory influences new architecture even today, it is important to understand it well.
Keywords: phenomenology; architecture; theory; Norberg-Schulz; modernity